2018
DOI: 10.1111/rda.13208
|View full text |Cite
|
Sign up to set email alerts
|

Proteome of the periovulatory oviduct and uterus of goats as related to nutritional balance

Abstract: This study was conducted to evaluate the effects of different feeding levels on the proteome of oviduct and uterus tissues of hormonally stimulated goats during the periovulatory period. Forty goats were separated into four different diet groups: Diet 1.0 M (n = 11), Diet 1.3 M (n = 10), Diet 1.6 M (n = 9), Diet 1.9 M (n = 10), fed with 1.0, 1.3, 1.6 and 1.9 times live weight maintenance, respectively. After four weeks of treatment, six hormonally stimulated females per treatment group were randomly selected f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
19
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 48 publications
(61 reference statements)
3
19
0
Order By: Relevance
“…Therefore, it is not surprising that the α-1-antiproteinase transcript has been identified in the oviductal cells [17], presumably secreted by the oviductal epithelium. Corroborating our results, Pillai et al, [44] identified α-1-antiproteinase and other serpins (A3-1, A3-7, A3-8, D1 and H1) in bovine OF, as well as Fernandes et al, [45], in the periovulatory oviduct and uterus of goats [44], and these genes are expressed by the porcine oviduct [46]. PGK1, a non-secreted enzyme, was found in a higher concentration in the OF of pregnant heifers.…”
Section: Discussionsupporting
confidence: 90%
“…Therefore, it is not surprising that the α-1-antiproteinase transcript has been identified in the oviductal cells [17], presumably secreted by the oviductal epithelium. Corroborating our results, Pillai et al, [44] identified α-1-antiproteinase and other serpins (A3-1, A3-7, A3-8, D1 and H1) in bovine OF, as well as Fernandes et al, [45], in the periovulatory oviduct and uterus of goats [44], and these genes are expressed by the porcine oviduct [46]. PGK1, a non-secreted enzyme, was found in a higher concentration in the OF of pregnant heifers.…”
Section: Discussionsupporting
confidence: 90%
“…However, there is evidence that metabolic perturbations encountered by the mother can alter this buffering function of the oviduct [97]. In goats, a modification of the nutritional balance in the diet altered the expression of proteins participating in apoptosis, antioxidant, and immunological activities in the periovulatory oviduct-functions important for embryo development [98].…”
Section: Metabolism and Energy Balancementioning
confidence: 99%
“…Comparison between four different diet groups identified seven differentially expressed proteins in ampullas of animals fed with 1.9 times live weight maintenance [98] Energy balance OEC gene expression Cattle…”
Section: Energy Balance Oec Proteins Goatmentioning
confidence: 99%
“…The Benjamini-Hochberg correction for multiple tests was further applied to adjust the derived p-values 18 . Only functional categories and pathways with p-values under a threshold of 0.05 were considered signi cant 19 .…”
Section: Data Processingmentioning
confidence: 99%